2014
DOI: 10.1093/toxsci/kfu090
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Genotoxicity of Ginkgo Biloba Extract in gpt Delta Mice and Constitutive Androstane Receptor Knockout Mice

Abstract: The National Toxicology Program study of Ginkgo biloba extract (GBE), a herbal supplement, reported concerns regarding genotoxicity and clear evidence of hepatocarcinogenicity and liver hypertrophy in mice. To clarify the genotoxicity of GBE in vivo, we performed reporter gene mutation assay using gpt delta mice. We also used a combined liver comet assay and bone marrow micronucleus assay using C3H-derived constitutive androstane receptor knockout (CARKO) and wild-type mice. No remarkable increases in gpt or S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…Additionally, MEG, a plant-derived phenylpropanoid chemical that is commonly used as a flavoring agent in food products, was selected because it bears structural resemblance to safrole, which is a known carcinogen (Bode and Dong, 2015). Our results and those of others verified that both of these compounds have carcinogenic activity, but indicated that their mechanisms of carcinogenesis may differ fundamentally in terms of their levels of genotoxicity (non-genotoxic for GBE; genotoxic for MEG) (Li et al , 2009, Umegaki et al , 2007, Hoenerhoff et al , 2013, Maeda et al , 2015, Maeda et al , 2014, Burkey et al , 2000, Miller et al , 1983, Zhou et al , 2007). Genotoxic or non-genotoxic classification of chemical compounds is based on various in vitro and in vivo genotoxicity assays (Smith et al , 2016), where genotoxic carcinogens induce DNA damage or mutations and non-genotoxic carcinogens do not directly alter DNA, but instead influence cellular transformation secondarily, in response to proliferative or metabolic effects.…”
Section: Introductionsupporting
confidence: 83%
See 1 more Smart Citation
“…Additionally, MEG, a plant-derived phenylpropanoid chemical that is commonly used as a flavoring agent in food products, was selected because it bears structural resemblance to safrole, which is a known carcinogen (Bode and Dong, 2015). Our results and those of others verified that both of these compounds have carcinogenic activity, but indicated that their mechanisms of carcinogenesis may differ fundamentally in terms of their levels of genotoxicity (non-genotoxic for GBE; genotoxic for MEG) (Li et al , 2009, Umegaki et al , 2007, Hoenerhoff et al , 2013, Maeda et al , 2015, Maeda et al , 2014, Burkey et al , 2000, Miller et al , 1983, Zhou et al , 2007). Genotoxic or non-genotoxic classification of chemical compounds is based on various in vitro and in vivo genotoxicity assays (Smith et al , 2016), where genotoxic carcinogens induce DNA damage or mutations and non-genotoxic carcinogens do not directly alter DNA, but instead influence cellular transformation secondarily, in response to proliferative or metabolic effects.…”
Section: Introductionsupporting
confidence: 83%
“…Furthermore, GBE induces hepatocellular hypertrophy in B6C3F1/N mice and modulates the expression of genes that control oxidative stress and proliferation (Hoenerhoff et al 2013). These findings are supported by mechanistic evaluation of GBE in constitutive androstane receptor knockout mice, which confirmed a predominant nongenotoxic mode of carcinogenicity (Maeda et al 2014(Maeda et al , 2015. However, results from in vitro bacterial gene mutation assays (Ames assays) that were performed using the same lot of GBE suggest that GBE is mutagenic to different bacterial strains (Hoenerhoff et al 2013).…”
Section: Discussionmentioning
confidence: 88%
“…Second, we wanted to build a bridge between previous and current animal studies and more human-relevant models. This was particularly important due to the speciesdependent activity of the CAR pathway (Lau et al, 2012, Cherian et al, 2015), which has been implicated in GBE hepatotoxicity (Maeda et al, 2014, Maeda et al, 2015. In vitro methods to compare various samples of the same botanical can be useful because they provide quick and human-relevant information (with the use of human cell lines), and they can be tailored to specific biological activities (e.g., CAR and PXR activity).…”
Section: Conclusion and The Path Forwardmentioning
confidence: 99%
“…Other side effects linked to G. biloba include allergic skin reactions and occasional anaphylaxis-like reactions following intravenous administration (De Smet, 2002). In a reporter gene mutation assay using gpt delta mice and a combined liver comet assay and bone marrow micronucleus assay using C3H-derived constitutive androstane receptor knockout (CARKO) and wild-type mice, there was no evidence of genotoxicity (Maeda et al, 2014). The gpt mice were exposed to a G. biloba extract at levels up to 2,000 mg/kg body weight per day for 13 weeks for the reporter gene mutation assays, and the CARKO and wild-type mice were exposed to doses up to 2,000 mg/ kg by daily gavage for 3 days.…”
Section: Safetymentioning
confidence: 99%